(untitled) (Revista de Ciências Agroveterinárias, 2009)
This work was set aiming to evaluate the adaptation of lemon grass (Cymbopogon citratus (D.C.) Stapf), citronela (C. wionterianus Jowit), palmarosa (C. martinii Stapf), giant lemon grass (C. flexuosus), and patchuli (Pogostemum cablin (Blanco) Bent) to the climatic conditions of the North Plateau of Santa Catarina, southern Brazil. The experiment was set in the city of Canoinhas, in December of 2006. A randomized block design, with three replicates, was used. The five aromatic tested species were planted in hills, with distances varying according to the species. Soil fertilization was carried out with the application of 100g of natural phosphate and 1000g of organic fertilizer per hill. The height growth and percentage of live plants were evaluated in six periods: one in the summer, three in the winter and two in the spring of 2007. Palmarosa, citronela and lemon grass showed high survival index and adequate height growth during the first five months after planting. All the species suffered severe frost damages in the winter and did not sprout again in the following spring. Therefore, the five tested species did not show adaptation for commercial cropping systems in the prevailing climatic conditions of North Plateau of Santa Catarina State.